Evaluating Flood Susceptibility through integrated Geospatial Techniques in Thailand’s Monsoon Regions - Ruthirako, Poonyanuch; Choosuk, Chanisada; Suwan-on, Kannipat; Thongpoon, Siriluck; Thongpoon, Kumpee; Thangrattanasuwan, Pattarin (Engineering, Technology & Applied Science Research, 2025)
This study integrated Geographic Information Systems (GIS) with the Potential Surface Analysis (PSA) method to assess and map flood hazards in the repeatedly flooded Khuan Khanun District of Phatthalung Province, Thailand. Amid the escalating global concerns about climate change impacts this research addressed critical gaps in local disaster preparation and resilience strategies demanded to face the increased precipitation and intensified flooding documented in recent IPCC reports. By synthesizing data considering multiple parameters such as slope, elevation, water and road density, land use, and soil drainage, this work delineated flood-prone areas, emphasizing their susceptibilities and the specific environmental dynamics that influence hydrological behavior. The findings revealed that over 66% of Khuan Khanun District fell within high to very high flood risk zones, accentuating the urgent need for enhanced flood mitigation measures. The significance of comprehensive flood risk management is hilighted, having incorporated advanced mapping techniques to inform effective policymaking and community-engaged planning, aiming to bolster regional resilience against recurrent threat of flooding.